Do ecological valid stop signals aid detour performance? A comparison of four bird species - Anneleen Dewulf; Clara Garcia-Co; Wendt Müller; Joah Robert Madden; An Martel; Luc Lens; Frederick Verbruggen (Royal Society Open Science)
Response inhibition (RI), or the stopping of actions, is considered a key component of flexible and adaptive behaviour. Across fields, RI is often treated as a unitary cognitive mechanism. However, we propose that RI consists of a chain of cognitive processes, including the detection of a stimulus, the selection of an appropriate behaviour (go or stop) and the implementation of it (execution or inhibition of a motor response). From this, we propose that individual variation in RI can arise at the early signal detection stage. This idea was tested in a detour barrier task, which is one of the most popular tools to study RI in non-human animals. The role of signal detection in detour tasks has been largely neglected, with a few notable exceptions. We therefore partially replicated two previous studies that manipulated the perceptual characteristics of the barrier, while addressing some conceptual and methodological shortcomings of the original work. Specifically, we compared how detour performance of four bird species (i.e. white leghorn chickens, Japanese quails, herring gulls and domestic canaries) is differently influenced by vertical-bar (VB) and horizontal-bar (HB) barriers. In contrast to the previous work, performance on the detour task did not improve when the perceptual characteristics of the barrier matched the ecological niche of the species. However, all species showed some level of learning, as evidenced by shorter detour latencies (except in herring gulls) and fewer persisting attempts. These findings highlight the need for replication studies and emphasize the importance of improving methodological and conceptual design factors to further investigate the underlying mechanisms of RI in animals. Preregistered Stage 1 protocol: https://osf.io/qvxgh (date of in-principle acceptance: 20/03/2023).